Metabolic and hemodynamic effects of unilateral tourniquet application on lower extremities of the patients with coronary artery disease - (:unkn) unknown (My University, 1997)
Objective: The aim of this study is to investigate the metabolic and hemodynamic effects of unilateral tourniquet application on lower extremities. Methods: Ten of the 20 patients had coronary artery disease and the remaining 10 patients without coronary artery disease were regarded as controls. The anesthesia was the same for both groups. Hemodynamic (SAP, DAP, MAP, HR, CVP), metabolic (K, CPK, CPK-MB, SGOT, LDH1, WBC), ETCO2, SpO2, body temperature, blood gas value and ECG changes were recorded. Results: SAP, DAP and MAP significantly decreased in the patients with coronary artery disease after removal of the tourniquet when compared to the measurements obtained during the application (p < 0.05). HR was not found to be significantly changed in the patients with coronary artery disease (p < 0.05). In the control group, HR decreased during the application and significantly increased after removal of the tourniquet (p < 0.05). A decrease in pH value and an increase in PCO2 and ETCO2 values were observed in both groups immediately and ten minutes after the removal of the tourniquet (p < 0.05). K, CPK, LDH1, SGOT, WBC were not found to be significantly changed in both groups (p > 0.05). CPK-MB increased in both groups (p < 0.05). Conclusion: Data obtained revealed that tourniquet application may cause hemodynamic and metabolic changes and monitorization is necessary particularly in the patients with coronary artery disease.
Keywords: Blood gas values; Coronary artery disease; ECG; Tourniquet